PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TIKTOK SHOP DI BANDA ACEH DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI - Atika Mardhiyah Simamora; Syarifah Evi Zuhra (Departemen Manajemen, 2023)
This study aims to see the effect of perceived ease of use, and perceived risk on Tiktok Shop consumers in Banda Aceh with Trust as a mediating variable. The sample used in this study was the Banda Aceh community who had made a purchase at the Tiktok Shop at least once, totaling 210 respondents. Data collection equipment used in this study is a questionnaire. The sampling technique used was purposive sampling technique. The analytical method used is Structural Equation Modeling (SEM). Based on the results of the SEM analysis, it was identified that perceived ease of use did not affect trust in Tiktok Shop consumers in Banda Aceh, perceived risk influences trust in Tiktok Shop consumers in Banda Aceh, perceived ease of use did not affect purchasing decisions in Tiktok Shop consumers in Banda Aceh, perceived risk influences purchasing decisions in Tiktok Shop consumers in Banda Aceh, trust influences purchasing decisions in Tiktok shop consumers in Banda Aceh, there is no effect of perceived ease of use on purchasing decisions with trust as a mediating variable on Tiktok Shop consumers in Banda Aceh and there is influence perceived of risk on purchasing decisions with trust as a mediating variable for Tiktok Shop consumers in Banda Aceh.